ANALYSIS OF THE EFFECTIVENESS OF THE MUKHTAR INSTITUTION IN CITY CENTERS IN TERMS OF PUBLIC ECONOMY IN TURKEY - Arzu Kızılkaya; Alparslan Uğur (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
With the effect of the developing world and globalization, the increasing human needs have become unlimited and the world has become a small local government. Demographic, social and societal developments have also brought innovations in management. The recent dominance of the welfare states understanding and the increasing importance of the modern management approach have led to an increase in the responsibilities of the state. The state alone has become unable to provide services to the entire public with only the central government, so the responsibilities of local governments have increased. The mukhtar institution, which is the closest point of the local government to the people and acts as a bridge between the people and the central-local government, has become an important unit. In this study, it has been evaluated in terms of public effectiveness whether the mukhtar institution has been successful as a state policy in Turkey, how much it can keep up with the digital age, and whether it can meet the needs especially in city centers. While making the evaluation, a questionnaire was applied to 410 participants over the internet (online), cross-table and chi-square analyzes were made with the help of the SPSS econometric analysis program with the data obtained from the survey results. As a result of the analyzes, it was concluded that the mukhtar institution in the city centers is not effective in the public economy and creates a waste of resources for the state.